2003
DOI: 10.1161/01.res.0000077044.60138.7c
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Stretch Enhances mRNA Expression and Proenzyme Release of Matrix Metalloproteinase-2 (MMP-2) via NAD(P)H Oxidase–Derived Reactive Oxygen Species

Abstract: Mechanical stretch is a hallmark of arterial hypertension and leads to vessel wall remodeling, which involves matrix metalloproteinases (MMPs). Because mechanical stretch is further capable of inducing reactive oxygen species (ROS) formation via the NAD(P)H oxidase, we assessed whether mechanical stretch enhances MMP expression and activity in a NAD(P)H oxidase-dependent manner. Therefore, vascular smooth muscle cells (VSMCs) isolated from C57BL/6 mice were exposed to cyclic mechanical stretch. The impact of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
256
3
11

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 382 publications
(296 citation statements)
references
References 35 publications
26
256
3
11
Order By: Relevance
“…Furthermore, Yamaguchi et al (30) reported that stretch-dependent Egr-1 activation enhances the expression of membrane type 1 matrix metalloproteinase in rat microvascular endothelial cells with a significant impact on angiogenesis by affecting the activity of matrix metalloproteinase-2. In this regard, we recently demonstrated that mechanical stretch enhances expression and release of matrix metalloproteinase-2 in a redox-sensitive manner (11).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Yamaguchi et al (30) reported that stretch-dependent Egr-1 activation enhances the expression of membrane type 1 matrix metalloproteinase in rat microvascular endothelial cells with a significant impact on angiogenesis by affecting the activity of matrix metalloproteinase-2. In this regard, we recently demonstrated that mechanical stretch enhances expression and release of matrix metalloproteinase-2 in a redox-sensitive manner (11).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the prominent increase of p47 phox mRNA and protein expression observed in 4-week-old SHRs in the vasculature, macula densa, and distal nephron demonstrates that oxidative stress precedes development of hypertension. Mechanical stretch of wild-type VSMCs resulted in ROS formation and p47 phox translocation to the plasma membrane followed by an increase in Nox1 transcripts (92). In addition, Ang II-stimulated p47 phox translocation through c-Src phosphorylation and enhanced activity of NAD(P)H oxidase in human VSMCs (328).…”
Section: Nistala Et Al 2062mentioning
confidence: 97%
“…But the signalling mechanisms by which cisplatin stimulation modulated MMP-2 expression in thyroid cells are not yet clear. Several studies suggest that reactive oxygen species (ROS) play a major role in the activation of MMPs [57,58], and that NAD(P)H oxidase activation, a major source of ROS, is a key event in this process [59]. We here show that the inhibition of NAD(P)H oxidase not only prevented cisplatin-induced ROS generation and increase of MMP-2, but also inhibited p38/MAPK and EGFR activation, caspase-7 proteolysis and the arise of the apoptotic intrinsic pathway (Fig.…”
Section: Muscella Et Al -Role Of Egfr In Cisplatin-treated Cells -16mentioning
confidence: 99%